Analisis Pola Komunikasi Siswa SMA Negeri 1 Mamasa - Tifa Mora; Fanny fandriany; Astriani Sanda; Nurul Syafirah; Nurisma Judar (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
The digital transformation in education has significantly reshaped communication patterns between students and teachers; however, its effectiveness remains a challenge, particularly at the secondary education level. This study aims to describe and analyze the tendencies of students’ digital communication patterns at SMAN 1 Mamasa. A descriptive quantitative approach was employed, involving 26 students as respondents. The data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics in the form of the mean value. The results indicate that all indicators fall within the moderate category, with the highest score on students’ reluctance to initiate communication with teachers (mean = 3.54) and the lowest on comfort in digital communication (mean = 2.96). Additionally, the use of informal language is relatively dominant (mean = 3.50) and contributes to potential misunderstandings in online communication (mean = 3.23). Social media also plays a significant role as a source of information (mean = 3.42). These findings suggest that digital communication is not yet fully effective, as it is influenced by psychological, linguistic, and cultural factors. This study highlights the importance of strengthening digital communication literacy and developing more adaptive academic communication strategies in school environments.